2016
DOI: 10.3347/kjp.2016.54.3.281
|View full text |Cite
|
Sign up to set email alerts
|

C3H/He Mice as an Incompatible Cholangiocarcinoma Model by <i>Clonorchis sinensis</i>, Dicyclanil and N-Nitrosodimethylamine

Abstract: Clonorchis sinensis is a Group-I bio-carcinogen, associated with cholangiocarcinoma (CCA). The hamster is the only experimental model of C. sinensis-mediated CCA, but we oblige another animal model. The present study intended to develop a C. sinensis (Cs) mediated CCA model using C3H/He mice, co-stimulated with N-nitrosodimethyl-amine (NDMA) and dicyclanil (DC). The mice were divided into 8 groups with different combinations of Cs, NDMA, and DC. Six months later the mice were sacrificed and subjected to gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…This may be due to insufficient NDMA dosage or/and its inconsistent uptake through drinking water. The same NDMA subcarcinogenic dose has also been reported in C. sinensis-associated CCA animal models in which NDMA administration alone did not cause any obvious histopathological changes in the livers of hamsters and mice [13,44]. Meanwhile, lesion severity and the levels of p47 phox and p67 phox immunoreactivities in livers of the C. sinensis plus NDMA-infected group were higher compared with the C. sinensis-infected group alone, indicating that they synergistically act on the liver deterioration as well as NOX activation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This may be due to insufficient NDMA dosage or/and its inconsistent uptake through drinking water. The same NDMA subcarcinogenic dose has also been reported in C. sinensis-associated CCA animal models in which NDMA administration alone did not cause any obvious histopathological changes in the livers of hamsters and mice [13,44]. Meanwhile, lesion severity and the levels of p47 phox and p67 phox immunoreactivities in livers of the C. sinensis plus NDMA-infected group were higher compared with the C. sinensis-infected group alone, indicating that they synergistically act on the liver deterioration as well as NOX activation.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this, the histopathologic changes (e.g., hyperplasia, peliosis, and extensive biliary fibrosis) in the livers of Cs plus NDMA mice were found. However, no CCA development was observed [44].…”
Section: Discussionmentioning
confidence: 91%
“…Studies have demonstrated that the strains and genetic background of mice are responsible for the susceptibility to C. sinensis infection. C57BL/6 J mice were believed to have the lowest susceptibility to C. sinensis infection compared with FVB, BALB/c and C3H/He mice [ 20 24 ]. In this study, we comparatively analysed the developing processes of C. sinensis and the iNOS/NO responses in TLR2 wild-type and mutant C57BL/6 J mice after the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that many strains of mice, including FVB/NJ (FVB) [ 20 22 ], BALB/c [ 8 , 9 , 20 – 23 ], and C3H/He [ 24 ] are susceptible to C. sinensis . By contrast, C57BL/6 mice are resistant to C. sinensis infection [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Также значимыми факторами риска являются первичный склерозирующий холангит / язвенный колит, хронические вирусные гепатиты С и В, носительство вируса Эпштейна -Барр, неалкогольная жировая болезнь печени, холелитиаз и (или) мальформации билиарной системы, отложения рентгеноконтрастных веществ (торотраст) в желчных протоках [27,28]. Существуют ýкспериментальные данные, свидетельствующие о том, что индуктором канцерогенеза в желчных протоках может послужить N-динитрозодиметиламин [29,30].…”
Section: источники данныхunclassified